The convection electrojet and the substorm electrojet - Y. Kamide; R. Nakamura (Annales Geophysicae, 1996)
Enhancements in the auroral electrojets associated with magnetospheric substorms result from those in either the electric field or the ionospheric conductivities, or both. Their relative importance varies significantly, even during a single substorm, depending on the location as well as on the substorm phases. It is predicted that different parts of the electrojets tend to respond in different ways to substorm activity. The unprecedented, unique opportunity for CLUSTER spacecraft observations of electric/magnetic fields and precipitating particles, combined with radar measurements of ionospheric quantities and with ground magnetometers, will provide us with crucial information regarding the physical nature of the separation between the "electric field-dominant'' and "conductivity-dominant'' auroral electrojets. This study also discusses the implications of these two auroral-electrojet components in terms of solar wind-magnetosphere-ionosphere interactions.